Buddhism Transformed: Religious Change in SriLanka - Venkatakrishna, B. V. (Journal of Dharma, 1992)
Richard Gombrich Gananath Obeysekere, "Buddhism Transformed"— Religious Change in SriLanka, Princeton: University Press, 1988, Pp. 1 6+484.